2018
DOI: 10.1007/s11606-018-4312-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Procalcitonin Guidance on Management of Adults Hospitalized with Chronic Obstructive Pulmonary Disease Exacerbations

Abstract: Utilizing PCT guidance in the management of COPD exacerbations was associated with a decreased total duration of antibiotic therapy and hospital LOS without negatively impacting hospital readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…The existence of comorbidity was not comparable between exposed and non-exposed groups in one study [18]. We were unsure about the comparability between their exposed and non-exposed groups for two studies [13,25].…”
Section: Quality Appraisal Of Clinical Studies Of Procalcitonin In Comentioning
confidence: 92%
See 3 more Smart Citations
“…The existence of comorbidity was not comparable between exposed and non-exposed groups in one study [18]. We were unsure about the comparability between their exposed and non-exposed groups for two studies [13,25].…”
Section: Quality Appraisal Of Clinical Studies Of Procalcitonin In Comentioning
confidence: 92%
“…A total of 14 studies were included in the metaanalysis of PCT as a biomarker for COPD exacerbation ( Fig. 1) [6,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Reasons for excluding studies are summarized in Supplementary Appendix 2; the most common reason for excluding a study was the lack of reported data specifically on COPD exacerbation.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For lower respiratory illnesses, these newer tests include rapid viral panels using PCR and the biomarker procalcitonin, the latter of which may be elevated in bacterial infections. The evidence is mixed for the benefit of procalcitonin to guide antimicrobial prescribing in acute exacerbations of COPD 12–15. C-reactive protein (CRP) is a biomarker that may be elevated in a variety of medical illnesses including infection.…”
Section: C-reactive Protein Testing To Guide Antibiotic Prescribing Fmentioning
confidence: 99%